Pengembangan Modul Pencemaran Udara Berbasis SETS (Science, Environment, Technology and Society) Terhadap Kemampuan Berpikir Kritis Siswa - Putri Febiola Siregar; Hasruddin; Tri Harsono (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to develop and examine the effect of a SETS-based (Science, Environment, Technology, and Society) Air Pollution Module in improving students’ critical thinking skills and scientific attitudes f tenth-grade students at SMA Muhammadiyah 1 Medan. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research instruments included test and non-test instruments, namely a modified BSNP-standard validation sheet and essay questions. The validation results indicate that the module is in the very feasible category, with average scores of 4.68 from material experts, 3.60 from media experts, and 4.00 from language experts. The results of classroom implementation show that the SETS-based module can improve students’ critical thinking skills, with an N-Gain score of 0.51 (moderate category). Furthermore, there is a significant effect of using the module on students’ critical thinking skills. Therefore, the SETS-based air pollution module is suitable for use as teaching material to support meaningful and contextual learning.